Doxology and loving knowledge in Augustine’s De doctrina christiana Book 1 - Harrison, C (Creighton University, 2018)
This paper will explore why Augustine persists in using the categories of signs and things and use and enjoyment, even though they give rise to so many difficulties and proved so inimical to what he actually wanted to say in Book 1 of De doctrina christiana. It argues that, in fact, these classical categories are subverted and transformed by Augustine’s treatment of the double commandment of love of God and love of neighbor and his conviction that God can ultimately be known only by a “knowledge of the heart” – one which leads, not to an exercise of the intellect but to doxology or praise of the unknowable, ineffable God. It takes issue with recent trends in Augustine scholarship, which, in examining Augustine’s debt to Stoicism, appear to have undermined his doctrine of grace and loving knowledge.